Optimization of the quinoa cooking process using the 3k design and the desirability function: Degree of gelatinization, water absorption index, solubility index and cotyledon detachment (Scientia Agropecuaria, 2020)
Optimization of the steam quinoa cooking process was carried out, using a response surface design (RSM) 3-level: 3k factorial, and the multiple response optimization methodology of the desirability function (Dx) was used to find the optimal region, which are improved tools to optimize the variables of a process, evaluate the maximization of the water absorption index (WAI), water solubility index (WSI), degree of gelatinization (GE) and the minimization of cotyledon detachment (DC) of quinoa (Chenopodium quinoa Willd). The equipment used was a vertical cook with a steam generator, the study cooking variables, the steam pressure, and the cooking time. The optimal process values were: Pressure 1.5 kgf.cm-2 and time 8 minutes for the best characteristics of cooked quinoa WSI of 26.411%, WAI of 7.960 (g.g-1), GE of 89.245% and CD of 18.40%, the value of the desirability function as an indicator of multiple responses was 0.798. Knowledge of these characteristics can be a valuable complement in the cooking process and thus contribute to improving the quality of cooked cereals.
Keywords: Chenopodium quinoa; steam cooking; optimization; response surface; factorial design.